Determination of antibodies to Caprine arthritis encephalitis virus in goats and sheep in some localities in Sudan - Ali, Wegdan Hassan; Saeed, Intisar Kamil; Mutwakil, Shaza Mohammed; Algezoli, Omer A.; Mohammed, Abdelgader Ballal; Ahmed, Ihsan Hussein; Elhassan, Sahar Mohammed; Ahmed, Baraa Abdelaziz; Asil, Rayan M. A.; Alsarraj, Saafass M. A.; Abdelgader, Abdelmhmoud Atalmanan; Ali, Yahia Hassan (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Caprine arthritis encephalitis (CAE) infection is existing worldwide causing economic loss in goat production. This work was conducted to investigate the prevalence of CAE in local and foreign goat breeds and sheep in different localities in Sudan. Materials and methods: A total of 368 sera samples were prepared; among these, 112 were collected from cross (n=39) and foreign (n=73) breeds of goat in Khartoum state, equal number of sera (n=23) were collected from goats and sheep from each of River Nile, Gedarif, Sinnar and North Kordofan states. Eighteen cross bred goats were tested from River Nile state. From foreign bred goats, 28 and 26 sera were collected from Gazira and Northern states, respectively. The collected sera were examined for the presence of antibodies to CAE virus using Enzymed-Linked Immunosorbent Assay (ELISA). Results: The overall seroprevalence of CAE was 2.99% (n=11/368). Positive results were found only in 11 of foreign breed of goats (Cyprus shami) collected from Gazira (39.29%; n=11/28). Statistically, there was an association between breed and location (P=0.001 and P=0.671, respectively). Conclusion: The CAE virus infection exists only in foreign goat breeds. Gazira state showed the highest seroprevalence as compared to other states considered in this study. Strict hygienic measures should be adopted to control the disease and to prevent its spread to local breeds. http://doi.org/10.5455/javar.2016.c154